Exposición por sulfatos en el suelo a los elementos superficiales de hormigón de viviendas del cantón Chambo, provincia de Chimborazo - Colcha Lescano, Luis Israel (2023)
The Chambo canton has an area of 163.4 km2 as established by the Association of Municipalities of Ecuador, however, in the entire territory there is only one urban settlement of 118.37 hectares, analysis of the concentration of sulfates in the soil without leaving aside the rest of the area of the canton.The general objective of this research project is to "Analyze the exposure by sulfates in the soil to the superficial concrete elements of houses in the Chambo canton, Chimborazo province, for which, based on the existing bibliography using a systematic method, it was determined 41 soil samples and the location of the points was georeferenced through the use of the ArcGIS software, in the areas where there was a higher concentration of houses, they were densified to improve the study, for which a total number of 53 samples was obtained, then The classification was carried out through the Unified Classification System (SUCS) test, in which soils were obtained as: Elastic Silt (MH), Sandy Silt (ML), Silty Sand (SM) and Clay Gravel with Sand (GC). In the analysis of sulfate concentration, results are presented according to the NEC standard: S0 not applicable, S2 Severe and S3 Very Severe. The durability of the concrete is negatively affected by the sulphate attack process, since it causes alterations in the chemical characteristics of the cement pastes and in the mechanical properties of the concrete, emphasizing that the exposure can vary due to the presence of other elements apart from the sulphates.